Australasian Rural Geographies: At the Core, in the Antipodes?. (7th October 2015) - ARGENT, NEIL
Abstract This paper reviews 'Antipodean' rural geography research published over the period 2012–2014 inclusive. A broad, inclusive stance was adopted to what should be regarded as Antipodean rural geography. Key publication outlets were identified and scanned for what were deemed to be relevant paper titles and abstracts, then the institutional and disciplinary affiliations of authors, bearing in mind a general concern for 'rural issues'. The review concentrates on the prominent themes of the recent mining boom and its externalities, new perspectives on agrarian and regional development, and population issues. Australasian rural geographers have not only become adept at 'writing back' to the centre but have played leading roles in the intellectual development of the sub‐discipline and cognate areas (e.g. rural sociology). Indeed, at least in the short period covered by this review and in the admittedly selective scope of that survey, Australian and New Zealand rural geographers have been at the forefront in advancing the sub‐discipline internationally. In doing so, they have not only placed the discussion of Australasian rural issues within a global context but have further refined the philosophical and conceptual approaches and tools used. In important respects, then, Australasian rural geographers are very much at the core of the international project of contemporary rural geography. Moreover, they have made – and continue to make – important contributions to the broader discipline of human geography.